Just in time. A philosophy applicable to small businesses (Ingeniería, Sostenibilidad y Sociedad, 2024)
This research delves into the Just in Time methodology, in order to understand it and explain the basic needs that are met, improve and other meanings with the aforementioned model. Due to the work format used in JIT, it can in turn improve sectors and characteristics of a company or company, avoiding or correcting inconveniences in production issues, where the amount of waste that was in the due processes, were unsustainable quantities for optimal profitability. Just-in-Time, you will make better use of the company's sections to avoid bottlenecks and an optimal state in profits.
Keywords: Just-in-Time; Bottlenecks; Optimization; Productivity